Physical And Chemical Characteristics Of Tropical Peats : A Review - Cynthia Casendra, Anak Nicholas Lembi (Universiti Malaysia Sarawak, UNIMAS, 2009)
This paper describes the physical and chemical characteristics of tropical peat. It covered mostly the tropics areas in the worldwide. All the analysis done by gets through others research. The data are collected from various types of sources. Study of physical properties was more the domain of soil mechanics and soil engineering than soil chemistry